2010
DOI: 10.1111/j.1349-7006.2009.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

CD44+ slow‐cycling tumor cell expansion is triggered by cooperative actions of Wnt and prostaglandin E2 in gastric tumorigenesis

Abstract: Similar to normal tissue stem cells, cancer stem cells (CSCs) are thought to be quiescent or slow-cycling and, thereby, insensitive to chemo-and radiotherapies. CD44, a cell surface component that interacts with the extracellular matrix, has been found to be highly expressed in CSCs of several solid tumors. However, the relevancy between CD44+ cells and slow-cycling cells and the underlying mechanisms for the emergence of CD44 + CSCs during tumorigenesis have not been elucidated. Here we show that a gastric gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 27 publications
7
106
0
Order By: Relevance
“…β-catenin is a downstream molecule in the Wnt signaling pathway and plays important roles in the structural organization and function of cell-to-cell adhesion and tumor invasion and metastasis (42). CD44 can also regulate Wnt-target genes (43). Among them, Akt is important for the survival of cancer cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin is a downstream molecule in the Wnt signaling pathway and plays important roles in the structural organization and function of cell-to-cell adhesion and tumor invasion and metastasis (42). CD44 can also regulate Wnt-target genes (43). Among them, Akt is important for the survival of cancer cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Because CD44 is a marker of normal and cancer stem cells, 28 we examined CD44 expression and differentiation status of epithelial cells in Tnf À / À Gan mouse tumors. In the Tnf þ / þ or Tnf þ / À Gan mouse tumors, CD44 mRNA levels increased significantly, by more than eightfold, the Figure 3a).…”
Section: Differentiation Of Tumor Cells By Tnf-a Gene Disruptionmentioning
confidence: 99%
“…Against this background, we evaluated whether Mcl-1 knockdown was effective for sensitizing chemotherapy-induced apoptosis in CSC-like populations in gastric cancer cells. We used a cell surface marker molecule, CD44, which is reported to be a CSC marker in gastric cancer [12][13][14][15][16][17], to identify chemotherapy-resistant subpopulations. We found that the Mcl-1 expression level was relatively high in CD44-positive gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%